2016
DOI: 10.1186/s12711-016-0267-0
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-reproducibility of genotypes from sheep technical replicates on Illumina and Affymetrix platforms

Abstract: BackgroundAccurate genomic analyses are predicated upon access to accurate genotype input data. The objective of this study was to quantify the reproducibility of genotype data that are generated from the same genotype platform and from different genotyping platforms.MethodsGenotypes based on 51,121 single nucleotide polymorphisms (SNPs) for 84 animals that were each genotyped on Illumina and Affymetrix platforms and for another 25 animals that were each genotyped twice on the same Illumina platform were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 8 publications
(14 reference statements)
6
22
0
Order By: Relevance
“…The lowest mean genotype concordance (61.6%) was observed for monomorphic SNP while the highest (98.89%) was observed for SNP with MAF > 0.05 to ≤ 0.10 (Table 3). The study of Berry et al (2016) observed similar results.…”
Section: The Genotype Concordance Rate Per Snp Between Sowpro90 and Ssupporting
confidence: 73%
See 2 more Smart Citations
“…The lowest mean genotype concordance (61.6%) was observed for monomorphic SNP while the highest (98.89%) was observed for SNP with MAF > 0.05 to ≤ 0.10 (Table 3). The study of Berry et al (2016) observed similar results.…”
Section: The Genotype Concordance Rate Per Snp Between Sowpro90 and Ssupporting
confidence: 73%
“…Similar mean genotype concordance rates were reported by other studies in livestock and humans. An evaluation of 49,859 SNPs in sheep samples (n = 84) genotyped by Illumina and Affymetrix platforms reported a 98.1% mean genotype concordance rate per SNP (Berry et al, 2016). This study reported that only a small proportion (~0.3%) of homozygous genotypes in one platform was called as alternate homozygous in the other platform.…”
Section: The Genotype Concordance Rate Per Snp Between Sowpro90 and Smentioning
confidence: 91%
See 1 more Smart Citation
“…evaluated the reproducibility of genotypes from the same SNP locus generated on technical duplicate samples for the same Illumina platform or different Illumina platforms. A total of 1,400 of the remaining SNPs in the present study, reported by Berry et al (2016) to not have 100% concordance on the same Illumina genotype platform, were not considered further. Neither were an additional 1,278 SNPs that had <100% concordance on different Illumina genotype platforms were considered (Berry et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1,400 of the remaining SNPs in the present study, reported by Berry et al (2016) to not have 100% concordance on the same Illumina genotype platform, were not considered further. Neither were an additional 1,278 SNPs that had <100% concordance on different Illumina genotype platforms were considered (Berry et al, 2016). Only flock book-recorded animals from the main breeds of Belclare (n = 1,074), Charollais (n = 2,778), Suffolk (n = 1,799), Texel (n = 3,056), and Vendeen (n = 683) were retained.…”
Section: Introductionmentioning
confidence: 99%